An Analysis of Marketing Strategies For PS Djeram Kretek Cigarette Products in Bima Regency - Ramli Ramli; Sri Ernawati; Rosa Yulianti (CV Edujavare Publishing, 2026)
The cigarette industry in Indonesia is one of the manufacturing sectors that has a strategic role in the national economy. This study aims to analyze the marketing strategy of PS Djeram Kretek Cigarettes in Bima Regency based on consumer perceptions using the marketing mix (4P) approach, which includes promotion, product quality, price, and place/distribution. The research employed a quantitative descriptive method with data collected through questionnaires distributed to 100 consumers of PS Djeram Kretek Cigarettes in Bima Regency. The sampling technique used was purposive sampling. Data were analyzed using validity and reliability tests, as well as descriptive statistical analysis with the assistance of SPSS version 25. The results indicate that all research instruments were valid and reliable. The price variable obtained the highest mean score of 4.3800, followed by promotion (4.3775), place/distribution (4.3175), and product quality (4.3150). All variables were categorized as very good. The overall grand mean score of 4.3475 demonstrates that the marketing strategy of PS Djeram Kretek is perceived very positively by consumers. The product's main competitive advantage lies in its affordable pricing, which aligns with consumers' purchasing power, supported by effective promotional activities, good product quality, and accessible distribution channels. These findings suggest that the implementation of the 4P marketing mix has been effective in enhancing the competitiveness of PS Djeram Kretek in Bima Regency.